2019
DOI: 10.1038/s41418-019-0421-7
|View full text |Cite
|
Sign up to set email alerts
|

TXNDC12 promotes EMT and metastasis of hepatocellular carcinoma cells via activation of β-catenin

Abstract: Metastasis is one of the main contributors to the poor prognosis of hepatocellular carcinoma (HCC). However, the underlying mechanism of HCC metastasis remains largely unknown. Here, we showed that TXNDC12, a thioredoxin-like protein, was upregulated in highly metastatic HCC cell lines as well as in portal vein tumor thrombus and lung metastasis tissues of HCC patients. We found that the enforced expression of TXNDC12 promoted metastasis both in vitro and in vivo. Subsequent mechanistic investigations revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 36 publications
6
68
0
Order By: Relevance
“…A series of transcriptional factors could drive EMT process and thereby tumor-initiation, metastasis, response to chemotherapy and immune evasion (26,27). Our previous work has demonstrated Zeb1 as a vital activator in thioredoxin domain-containing protein 12-mediated EMT process of HCC (28). In the present work, we demonstrated that EMT process was dispensable for NCSTN-regulated HCC cell growth and metastasis, and Zeb1 was the key activator involved.…”
Section: Discussionsupporting
confidence: 55%
“…A series of transcriptional factors could drive EMT process and thereby tumor-initiation, metastasis, response to chemotherapy and immune evasion (26,27). Our previous work has demonstrated Zeb1 as a vital activator in thioredoxin domain-containing protein 12-mediated EMT process of HCC (28). In the present work, we demonstrated that EMT process was dispensable for NCSTN-regulated HCC cell growth and metastasis, and Zeb1 was the key activator involved.…”
Section: Discussionsupporting
confidence: 55%
“…Upregulated expression of LINC00978 is a marker of poor prognosis in HCC (Xu X. et al, 2019). In addition, elevated expression of TXNDC12 has been correlated with elevated expression of nuclear β-catenin and with OS and disease-free survival (Yuan et al, 2019). These studies indicated that next-generation sequencing could be performed to distinguish the biomarkers of HCC.…”
Section: Introductionmentioning
confidence: 93%
“…Epithelial to mesenchymal transition (EMT), a process that epithelial cells lose their polarized organization and acquire migratory and invasive capabilities, is considered to contribute to cancer metastasis ( 11 , 12 ). Therapeutics targeted to EMT pathway show a great potential for preventing tumor dissemination or sweeping off metastatic cancer cells in patients in advanced stage ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%